Rhexoacrodictys melanospora sp. nov. (Rhexoacrodictys, Pleurotheciales) from Yunnan, China - Bao, Shu-Xin; Xu, Rong-Ju; Zhu, Ying-An; Zhao, Qi (Phytotaxa, 2023)
Based on the morphological and phylogenetic analyses, we introduce a new species, Rhexoacrodictys melanospora, collected on decaying wood from terrestrial habitats in Yunnan, China. Phylogenetic analyses based on the combination of four loci (LSU, SSU, ITS and RPB2 data) demonstrated high support for establishing a new species within Rhexoacrodictys. The morphological characteristics of R. melanospora and the differences compared with the members of Rhexoacrodictys are also given in detail herein.